Atención al cliente y su incide.ncia en los ingresos de los socios de la compañía de transporte en tricimotos “URDATRICI S.A. periodo 2023. - Obando Rocafuerte, Genesis Janina (2024)
Not paying enough attention to the user will bring some consequences such as the loss of customers due to dissatisfaction with the service received, discrediting the image of the company and its economic life, for this reason the purpose of the study is to analyze the attention to the user. client and its impact on the income of the partners of the tricycle transportation company URDATRICI S.A. Of which a descriptive study with a mixed approach (qualitative and quantitative) is proposed through a non-experimental design supported by interviews and surveys with an observation guide applied to a sample of 63 partners and 270 clients of the transport company URDATRICI S.A. The presented result highlights the importance of customer service as a crucial factor through the value of Spearman's correlation coefficient r=0.364, which is interpreted that between both variables they have a medium positive correlation, which can emphasize aspects such as: Comfort, training, internal evaluations, the appearance of the units, the use of positive language and problem-solving abilities have a significant impact on user preference. Concluding that levels of satisfaction in relation to customer service have a direct impact on the economic growth of the company, therefore, investing in quality customer service is a fundamental strategy for long-term success.